2008
DOI: 10.1002/ijc.23971
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer in first‐ and second‐degree relatives of testicular germ cell tumor cases and controls

Abstract: Risk factors for testicular germ cell tumors (TGCT) have not been well identified; however, data suggest that risks of cancer in family members of men with TGCT is elevated. Using family history data from 738 cases and 904 controls enrolled in the U.S. Servicemen's Testicular Tumor Environmental and Endocrine Determinants (STEED) Study from 2002 to 2005, the risk of cancer in first-and second-degree family members of these men was examined. Relative risks (RRs) and 95% confidence intervals (CIs) were estimated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 28 publications
(93 reference statements)
1
9
1
Order By: Relevance
“…Results from a Swedish study population similarly suggested a slightly increased risk of testicular cancer in association with familial NHL,10, 11 which to our knowledge is the only previous investigation of this association. Furthermore, we observed a borderline statistically significant association between familial esophageal cancer and testicular cancer, which is in agreement with prior studies 10, 17. A similar tendency was found in a previous Danish study of cases from an earlier time period, however statistically insignificant and based on very few cases 9.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Results from a Swedish study population similarly suggested a slightly increased risk of testicular cancer in association with familial NHL,10, 11 which to our knowledge is the only previous investigation of this association. Furthermore, we observed a borderline statistically significant association between familial esophageal cancer and testicular cancer, which is in agreement with prior studies 10, 17. A similar tendency was found in a previous Danish study of cases from an earlier time period, however statistically insignificant and based on very few cases 9.…”
Section: Discussionsupporting
confidence: 93%
“…Although an association, thus, has been established between the risk of testicular cancer and testicular cancer in first‐degree relatives, it is an open question whether an association also exists between risk of testicular cancer and nontesticular cancers in relatives. Such possible associations were explored in previous studies of which some indicated higher risk of testicular cancer in association with, among others, cancers of the pancreas, esophagus, genitals and breast as well as melanomas and lymphomas, whereas other studies did not find such associations 7–12, 16–19…”
mentioning
confidence: 99%
“…Genetic factors contribute significantly to TGCT susceptibility as exemplified by a 4- to 15-fold increased risk in the sons and brothers of affected men, respectively [8,9]. With conventional inheritance however, risk should be similar in sons and brothers.…”
Section: Introductionmentioning
confidence: 99%
“…Susceptibility to testicular germ cell tumors (TGCTs) is illustrative (2). Testicular cancer is the most common malignancy affecting young men (3), more than 90% of testicular cancers result from TGCTs (4), TGCTs rank third in heritability among all cancers (5), and family history is the strongest known risk factor with a two-to sixfold increase among sons and a 5-to 19-fold increase among brothers of affected individuals (6)(7)(8)(9). Despite the strong evidence for heritability, the only TGCT susceptibility factors identified in genome-wide association studies are the gr/gr deletion on the Y chromosome and autosomal variants in KITLG, SPRY4, BAK1, and DMRT1, which together account for less than 10% of risk (10)(11)(12)(13)(14).…”
mentioning
confidence: 99%